PENGARUH AROMA TERAPI LEMON TERHADAP PENURUNAN INTENSITAS NYERI PADA PASIEN POST OPERASI DI RUANG RAWAT BEDAH - Fitri Zulaina, Rahma (Media Husada Journal Of Nursing Science, 2024)
Surgery is a service action for emergency cases in hospitals. Services can cause pain which results in the patient feeling afraid of being able to move or mobilize which can reduce the quality of life, and pain is even a source of frustration. The aim of this research is to determine the effect of lemon aroma therapy on reducing pain intensity in post-operative patients in the operating room at Haji Abdoel Madjid Batoe Batanghari Hospital in 2023. This research uses a pre-experimental research design of one - group pre test-post test design, the population of all patients post-operative surgery room at Haji Abdoel Madjid Batoe Hospital with a total of 134 respondents and a sample of 18 respondents using purposive sampling technique. Data analysis used the T-Test. The instrument used in this research used the Numeric Rating Scale (NSR) observation sheet. The research results showed that on average pre-test 5.11 respondents experienced moderate pain after being given lemon aromatherapy, 2.28 respondents experienced mild pain. The results of the Paired Sample T-Test showed that there was an effect of reducing pain intensity before and after being given lemon aromatherapy with a p-value of 0.000 (<0.05). It is hoped that the hospital can apply lemon aromatherapy as a non-pharmacological therapy that can be used to reduce pain in patients after surgical operations.